1987
DOI: 10.1111/j.1469-7610.1987.tb00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Abilities and Behavioural Characteristics of Children With Idiopathic Infantile Hypercalcaemia

Abstract: An investigation of the psychological characteristics of 44 children aged 6-16 years with documented evidence of idiopathic infantile hypercalcaemia revealed cognitive abilities and behavioural patterns which distinguish these children from other mentally handicapped groups. The children were all mildly to severely mentally handicapped, but exhibited superior verbal skills compared to their visuo-spatial and motor abilities. They showed high rates of behavioural disturbance, particularly in terms of hyperactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
125
5
9

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(152 citation statements)
references
References 16 publications
13
125
5
9
Order By: Relevance
“…Jones & Smith, 1975;Lenhoff, Wang, Greenberg, & Bellugi, 1997;Wang, Doherty, Rourke, & Bellugi, 1995). Psychological and behavioural markers include mild-moderate intellectual disability (ID; Udwin, Yule, & Martin, 1987), a sociable disposition (e.g. Jones et al, 2000), heightened anxiety (Dykens, 2003) and hyper-sensitivity to sound (e.g.…”
Section: Aetiological and Cognitive Characteristics Of Williams And Dmentioning
confidence: 99%
“…Jones & Smith, 1975;Lenhoff, Wang, Greenberg, & Bellugi, 1997;Wang, Doherty, Rourke, & Bellugi, 1995). Psychological and behavioural markers include mild-moderate intellectual disability (ID; Udwin, Yule, & Martin, 1987), a sociable disposition (e.g. Jones et al, 2000), heightened anxiety (Dykens, 2003) and hyper-sensitivity to sound (e.g.…”
Section: Aetiological and Cognitive Characteristics Of Williams And Dmentioning
confidence: 99%
“…Given the rarity of this genetic syndrome, many studies have reported results based on small samples, with participants spanning a wide age range, and variability in performance has been often overlooked in interpreting empirical results. At the outset, interest in the syndrome was sparked by case studies of unusual social and linguistic behaviour (e.g., Bellugi, Bihrle, Neville, Jernigan, & Doherty, 1992;Bellugi, Marks, Bihrle, & Sabo, 1988;Udwin, Yule, & Martin, 1987), which led researchers to search for spared abilities in the context of general mental retardation and of severe specific cognitive deficits in visual-spatial construction skills. This paper focuses on the social component of the WMS profile, addressing the question of whether the unusual sociability and friendly personality characteristic of people with this neurodevelopmental disorder (Gosch & Pankau, 1994;Jones et al, 2000;Mervis & KleinTasman, 2000) is associated with relatively spared abilities in decoding mental state information from nonverbal facial cues.…”
mentioning
confidence: 99%
“…Some of the earliest reports surfaced 20 years ago, with descriptions of exaggerated startle response to sound and anticipatory anxiety related to loud noise (Dilts et al, 1990). Although sensory modulation difficulties have been frequently noted in this population (e.g., Gosch & Pankau, 1994, 1997Leyfer et al, 2006;Udwin, 1990;Udwin et al, 1987), there have been few attempts to understand the nature of sensory-related problems. John and Mervis (2010) explored sensory problems in children with WS using the Short Sensory Profile (McIntosh, Miller, Shyu, & Dunn, 1999).…”
Section: Anxiety In Individuals With Williams Syndromementioning
confidence: 99%
“…Specifically, studies have shown that individuals with WS have difficulty with inhibitory control as indexed by measures of hyperactivity, approach, and attention seeking behaviors (Arnold et al, 1985;Dilts et al, 1990;Dykens & Rosner, 1999;Klein-Tasman & Mervis, 2003;Tomc et al, 1990;Udwin, 1990;Udwin et al, 1998;Udwin & Yule, 1991). Individuals with WS also have been shown to demonstrate difficulties with set-shifting and emotion regulation, as indexed by measures of low adaptability, high preoccupations, low persistence, high levels of stress reaction, and increased temper tantrums Klein-Tasman & Mervis, 2003;Tomc et al, 1990;Udwin, 1990;Udwin et al, 1987).…”
Section: Anxiety In Individuals With Williams Syndromementioning
confidence: 99%
See 1 more Smart Citation